Whose Health Matters? Longitudinal Analyses of Older Romantic Couples’ Health, Physical Capabilities, and Sexual Experiences - Park, Yoobin; Stenlund, Säde; Steptoe, Andrew (Oxford University Press (OUP), 2026)
Objectives
While considerable work has linked sexual activity to health and well-being in later life, the role of an individual’s physical health conditions in shaping their own and their partner’s later sexual experiences remains underexplored. This research examined concurrent and prospective dyadic effects of health and physical capabilities on sexual experiences.
Methods
We used two-wave data from 1,301 heterosexual couples (N = 2,602) in the English Longitudinal Study of Ageing. Multilevel models were fitted, estimating the association of both partners’ self-rated health, grip strength, and gait speed with sexual interest, activity, and satisfaction concurrently and four years later. Various sociodemographic and psychosocial covariates were adjusted in addition to the baseline outcome levels in longitudinal models.
Results
Both individuals’ and partner’s baseline self-rated health were positively related to intercourse frequency concurrently and at follow-up. Higher self-rated health was also associated with greater sexual satisfaction at follow-up across gender, but its positive associations with concurrent and later sexual interest were observed only among men. Men’s slower gait speed was linked to lower sexual interest for both partners at baseline and to women’s reduced sexual satisfaction at follow-up. Grip strength also showed some gender-specific associations with interest and intercourse frequency.
Discussion
Sexual experiences in later life appear to be shaped by both partners’ physical health conditions, with notable gendered patterns. These findings underscore the importance of considering both individual and dyadic health factors in supporting sexual interest and activity in later life, as well as identifying objective markers that may precede declines in sexual health.